Receptor Characterization and Functional Activity of Pyrokinins on the Hindgut in the Adult Mosquito, Aedes aegypti - Lajevardi, Aryan; Paluzzi, Jean-Paul V. (Frontiers in Physiology, 2020)
Pyrokinins are structurally-related insect neuropeptides, characterized by their myotropic, pheromonotropic and melanotropic roles in some insects, but their function is unclear in blood-feeding arthropods. In the present study, we functionally characterized the pyrokinin-1 and pyrokinin-2 receptors (PK1-R and PK2-R, respectively) in the yellow fever mosquito, Aedes aegypti, using a heterologous cell system to characterize their selective and dose-responsive activation by members of two distinct pyrokinin subfamilies. We also assessed transcript-level expression of these receptors in adult organs and found the highest level of PK1-R transcript in the posterior hindgut (rectum) while PK2-R expression was enriched in the anterior hindgut (ileum) as well as in reproductive organs, suggesting these to be prominent target sites for their peptidergic ligands. In support of this, PRXa-like immunoreactivity (where X = V or L) was localized to innervation along the hindgut. Indeed, we identified a myoinhibitory role for a PK2 on the ileum where PK2-R transcript was enriched. However, although we found that PK1 did not influence myoactivity or Na+ transport in isolated recta, the PRXa-like immunolocalization terminating in close association to the rectal pads and the significant enrichment of PK1-R transcript in the rectum suggests this organ could be a target of PK1 signaling and may regulate the excretory system in this important disease vector species.